Pengaruh Streamer Product Knowledge, Social Presence of Streamers, dan Social Presence of Viewers terhadap Kepercayaan Pelanggan Fashion Muslim di Live Shopping TikTok Live - Awlyasari, Dilta; Susilowati, Fitriah Dwi (Jurnal Ekonomika dan Bisnis Islam, 2024)
The purpose of this study is to analyze the influence of streamer product knowledge, social presence of streamers, and social presence of viewers on muslim fashion customers' trust in TikTok Live shopping. The number of Muslim fashion enthusiasts in Indonesia continues to increase every year. Shopping activities are also getting easier with the presence of online shopping services through live shopping, especially TikTok Live. The research method uses quantitative methods with primary data sources obtained from distributing questionnaires online. Sampling used purposive sampling technique with a total of 165 respondents. The technique used in data analysis is Structural Equation Modeling - Partial Least Square (SEM-PLS) in SmartPLS 4 software. The results of the research show that there is a positive and significant influence on streamer product knowledge, social presence of streamers, and social presence of viewers on muslim fashion customers' trust at TikTok Live shopping in the city of Surabaya. Muslim fashion marketers in TikTok Live shopping should be able to better master product specifications, be confident, have a good attitude and be communicative with viewers.